2016
DOI: 10.1682/jrrd.2014.12.0307
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of oxygen uptake during walking in ambulatory persons with multiple sclerosis

Abstract: Abstract-People with multiple sclerosis (MS) have an increased rate of gross oxygen uptake (gross-VO 2 ) during treadmill walking, and their gross-VO 2 may further vary with walking impairment. This study attempted to develop an equation for predicting gross-VO 2 from walking speed and an index of walking impairment in persons with MS and examine its accuracy. Gross-VO 2 was measured with open-circuit spirometry in 43 persons with MS (47 +/-9 yr; 38 women) during five treadmill walking trials, each lasting 6 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Results of overground and treadmill walking studies are presented in Figure 2c and Figure 2d, respectively. The range in walking speeds in overground conditions 28,30,39,41,[43][44][45][46][47][48][49][50][51][52][53][54][55] was lower, compared with treadmill walking, [33][34][35]56 with speeds between 0.43 and 1.48 m/s with Cw values between 0.16 and 0.44 mL O 2 /kg/m. The majority of the treadmill speeds were set at a predetermined velocity, ranging from 0.28 to 1.79 m/s, with concurring Cw values from 0.14 to 0.44 mL O 2 / kg/m.…”
Section: Cost Of Walking Of Overground Versus Treadmill Walking In Pwmsmentioning
confidence: 80%
See 1 more Smart Citation
“…Results of overground and treadmill walking studies are presented in Figure 2c and Figure 2d, respectively. The range in walking speeds in overground conditions 28,30,39,41,[43][44][45][46][47][48][49][50][51][52][53][54][55] was lower, compared with treadmill walking, [33][34][35]56 with speeds between 0.43 and 1.48 m/s with Cw values between 0.16 and 0.44 mL O 2 /kg/m. The majority of the treadmill speeds were set at a predetermined velocity, ranging from 0.28 to 1.79 m/s, with concurring Cw values from 0.14 to 0.44 mL O 2 / kg/m.…”
Section: Cost Of Walking Of Overground Versus Treadmill Walking In Pwmsmentioning
confidence: 80%
“…The cost of walking at multiple speeds of all pwMS is represented in Figure 2a including 29 studies. The minority of these studies (n = 6) presented data of the Cw at higher speeds (>1.44 m/s), [30][31][32][33][34]…”
Section: Cost Of Walking Of All Studies Including Pwmsmentioning
confidence: 99%
“…This is generally expected because DS is a condition that can impact physiological systems in diverse ways and to a different extent between people (Bull & Committee on Genetics, ). Thus, our results indicate a need to consider other variables—not measured in our study—for capturing the variability in VO 2 responses among individuals with DS; one such predictor could possibly be an index of mobility difficulties as it has been previously found in adults with multiple sclerosis (Agiovlasitis, Sandroff, & Motl, ). Nonetheless, the accuracy of the models was high, and the equations appear valid for practice.…”
Section: Discussionmentioning
confidence: 61%
“…All included studies reported at least one measure of absolute intensity (METs) and one relative measure of intensity (%HRR, %VO 2 R, %HR max, %VO 2max, HR index, lactate threshold, ventilatory threshold). However, four studies were excluded from the assessment of agreement when based on the reported means [ 23 , 43 , 51 , 54 ] because either, the absolute and relative values reported in these studies could not be directly compared using the ACSM intensity classification scheme [ 10 ] or mean and SD data were not reported. A further three studies were excluded from the assessment of agreement based on the reported means, either because the data from these studies were used in the comparison of agreement based on raw data [ 35 , 36 , 51 ] or used in the meta-regression [ 23 , 35 , 36 , 51 ] This resulted in eight studies being examined for agreement when based on mean values [ 44 48 , 50 , 52 , 53 ].…”
Section: Resultsmentioning
confidence: 99%